2014
DOI: 10.1118/1.4870964
|View full text |Cite
|
Sign up to set email alerts
|

Exploring potential mechanisms responsible for observed changes of ultrasonic backscattered energy with temperature variations

Abstract: Purpose: Previous studies have provided the observation that the ultrasonic backscattered energy from a tissue region will change due to a change of temperature. The mechanism responsible for the changes in backscattered energy (CBE) with temperature has been hypothesized to be from the changes in scattering properties of local aqueous and lipid scatterers. An alternative mechanism is hypothesized here to be capable of producing similar CBE curves, i.e., changes in speckle resulting from changes in summation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In three mouse tumors heated from 37.5 to 43°C with HIFU, after motion compensation, the means of image pixels with positive CBE monotonically increased by a mean of 3.5 dB (3.1 to 3.6 dB); the negative CBE monotonically decreased by −3.4 dB (−2.0 to −4.5 dB). Li et al reported similar findings for small transducer displacements in both elevation and axial directions (140). Breaking from the motion- and echo shifted-compensation CBE paradigm though, Tsui and colleagues proposed in 2012 that CBE imaging without echo shifting may have improved sensitivity to increased temperature detection (141).…”
Section: Specific Strategies For Ultrasound Thermometry and Ablatimentioning
confidence: 55%
“…In three mouse tumors heated from 37.5 to 43°C with HIFU, after motion compensation, the means of image pixels with positive CBE monotonically increased by a mean of 3.5 dB (3.1 to 3.6 dB); the negative CBE monotonically decreased by −3.4 dB (−2.0 to −4.5 dB). Li et al reported similar findings for small transducer displacements in both elevation and axial directions (140). Breaking from the motion- and echo shifted-compensation CBE paradigm though, Tsui and colleagues proposed in 2012 that CBE imaging without echo shifting may have improved sensitivity to increased temperature detection (141).…”
Section: Specific Strategies For Ultrasound Thermometry and Ablatimentioning
confidence: 55%
“…Other ultrasound approaches to ablation monitoring have been based on tissue echogenicity changes, including conventional B-mode imaging 6,12 as well as quantitative tracking of echo energy changes (e.g., integrated backscatter) [29][30][31][32] and statistical parameters of the backscattered ultrasound echoes. 33,34 However, the local echogenicity of tissue is dependent on heat-induced changes in tissue attenuation, sound speed, and bubble activity, which do not consistently correspond with local tissue coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…1,34,35 Echo decorrelation imaging, which tracks stochastic changes in echo waveforms over short time scales (e.g., 10-50 ms), 1,2 may potentially be a more robust predictor of ablation. Other ablation monitoring approaches have also tracked stochastic changes in echo signal amplitude or energy [32][33][34] but over longer time scales (e.g., comparison of speckle statistics between frames temporally separated by 20 s), 33 so that these approaches may not be suitable for in vivo monitoring in the presence of tissue motion. Experimental studies of echo decorrelation imaging have indicated that, in comparisons using the same ex vivo and in vivo echo data, local tissue ablation was predicted with significantly greater accuracy using echo decorrelation than using integrated backscatter.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature monitoring by means of intensity was reported to be effective in several works [6][7][8]. In our case, intensity was the best individual parameter.…”
Section: Discussionmentioning
confidence: 74%
“…To monitor temperature variations, several US-based methods were proposed. First of all, the change in signal's backscattered energy (CBE) was reported as a good temperate indicator in several studies [6][7][8]. CBE is based on the fact that heating modifies acoustic impedance of the tissue and subsequently the reflectivity [9].…”
Section: Introductionmentioning
confidence: 99%